O poder político como Agon - O agonismo do jogo e o antagonismo do enfrentamento - Silva, Natália Pereira Ribeiro da (2024)
The main objective of this study is to understand and analyze political power as Agon, whose meaning refers to struggle, competition and play, enabling us to distinguish between two categories of power: as “agonism and play” and as “antagonism and confrontation”. . To clarify this distinction we resort to the perspective of two contemporary thinkers. On the one hand, Chantal Mouffe (1996) introduces a conception of combative pluralism under the influence of the Nietzschean notion of “war of the gods”, as for her it is necessary to recognize the limits of pluralism, admitting that there is no “us” without the creation of a "they". From this perspective, Mouffe's central arguments develop through the distinction between (i) “politics” (in the “agonistic” sense of dispute and game), as the set of practices and institutions through which an order is created, thus revealing a shared symbolic terrain, whose presence of the “adversary” is fundamental and necessary for the agon to continue; and (ii) the “political” (as antagonism, presupposing a belligerent spirit, of real combat or war), understood as constitutive of human societies and calling into question the impossibility of common ground between the antagonists. On the other hand, Michel Foucault establishes two definitions of politics: (i) one as a “game” of the different arts of governing; and (ii) the other as “confrontation”, politics as clash and/or shock. Foucault analyzes, in the course In Defense of Society (1975-1976), the paradigm of “war” as an eventual principle in the analysis of power relations. This empirical working hypothesis, called “Nietzsche's Hypothesis”, aims to understand to what extent the binary scheme of war, struggle and confrontation of forces, can be effectively identified as the foundation of social relations, at the same time a principle and driving force for the exercise of political power. This frame of reference allows a comparison between Mouffe and Foucault, verifying to what extent their political categories (agonism/antagonism and game/confrontation) come closer or further apart in their meanings, also considering the reference to Nietzsche as a common point, whether as theoretical contribution or as a working hypothesis.